Teacher and his school - Doll, Emma Phillipine (My University, 1898)
Introduction: It is in the common school that the foundation of our education is laid. Someone has well said, “the establishment and liberal support of common schools should be objects of special interest to every citizen of our Union. On them depend the general diffusion and perpetuity of those great national blessings, and privileges which tend to the true exaltation of a people. Free schools are the nurseries of the public mind. They are the best safe guards against all the ills of ignorance and vice. The character of those who graduate from them must determine what the general condition of our country shall be. So long as more than nine tenths of our whole population never gains access to the advantages of our colleges, how important is it that the common school be properly cared for! How important is it that they be so sustained that they will send forth those healthful influences which shall be for the healing and preservation of the nation!” The common schools should be raised to a higher plane of knowledge and liberty. How shall this be done? Will not this plane be reached by giving to the rising generation that thorough instruction and training in all of the elementary branches- thus laying a firm foundation upon which to build a strong character and setting for them a high standard of excellence which by diligent striving they can attain? Does it not become the duty then, of the teacher to set this standard and of the parents to lend their ablest assistance in helping to carry it out? Then will they be prepared to honorably and successfully fulfil every duty which falls upon them after entering the broad world of experience. It has been said, “The hand that rocks the cradle, guides the footsteps of the nation.”
Citation: Doll, Emma Phillipine. Teacher and his school. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: School; Education; Knowledge; Liberty; Teacher; Theses; Manuscripts (documents)